Aplicación para el apoyo de procesos de rehabilitación en pacientes con daño cerebral utilizando realidad virtual - Montero Corzo, Jesús David (Universidad Antonio Nariño, 2022)
After conducting an investigation of cognitive functioning and psychopathological alterations in relation to quality of life in people undergoing medical treatment for stroke six and twelve months after hospital discharge, UAN researchers have concluded that it affects the cognitive processes in most people. This does not allow them to carry out the activities that they previously carried out normally, reducing their quality of life. In order to mitigate the problem, a Virtual Reality application was developed, where the patient can carry out activities related to the cognitive process to be treated. It should be noted that this application helps patients in their rehabilitation process, but it does not solve the conditions acquired after the stroke. The development of this application was carried out using the agi development methodology, each of these with a duration of 3 weeks. l SCRUM through 4 Sprints